Geopolitical Discourse In Translation - Mamarasulova, Gulnoz (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article examines the nature, structure, and communicative functions of geopolitical discourse as reflected in media texts and translation studies. It explores how geopolitical narratives are constructed through language and ideology, emphasizing their pragmatic and socio-cultural dimensions. The study also analyses how key geopolitical terms operate within specific contexts, revealing how semantic nuances shift across languages and cultures. Furthermore, it discusses the intertextual variations between original and translated texts, showing how translation mediates and re-frames geopolitical meanings. Drawing on discourse analysis, pragmatics, and translation theory, the paper argues that translation is not merely linguistic substitution but an act of ideological negotiation within the global information space.